Parents' and carers' views on factors contributing to the health and wellbeing of urban Aboriginal children - Hilary M. Miller; Christian Young; Janice Nixon; Melissa Talbot‐McDonnell; Mandy Cutmore; Allison Tong; Jonathan C. Craig; Susan Woolfenden (Elsevier, 2020)
Abstract Objective: To identify and describe caregiver perspectives on factors important for the health and wellbeing of urban Aboriginal children. Methods: Caregivers of Aboriginal children participating in the Study of Environment on Aboriginal Resilience and Child Health (SEARCH) were asked to describe the single most important factor that would help their children to be healthy and well. Responses were analysed using thematic and content analysis. Results: Of the 626 carers in SEARCH, 425 (68%) provided a response. We identified 13 factors related to: loving family relationships, culturally competent healthcare, food security, active living, community services, education, social and emotional connectedness, safety, breaking cycles of disadvantage, housing availability and affordability, positive Aboriginal role models, strong culture, and carer wellbeing. Conclusions: Aligning with holistic concepts of health, caregivers believe that a broad range of child, family and environmental‐level factors are needed to ensure the health and wellbeing of Aboriginal children. Implications for public health: This study highlights the importance of providing public health initiatives that enable equal access to the social determinants of health for carers of Aboriginal children. Affordable and adequate housing, food security, culturally appropriate healthcare, and family and community connectedness remain critical areas for targeted initiatives.